2002
DOI: 10.1111/j.1572-0241.2002.05995.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of obesity to hepatitis C-related fibrosis progression

Abstract: Obesity, advanced age at infection, and elevated ALT levels predict rapid disease progression, suggesting that measures aimed at weight reduction may play a significant role in hepatitis C management. The natural history of hepatitis C is independent of the presence of autoimmunity markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
129
4
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(142 citation statements)
references
References 21 publications
7
129
4
2
Order By: Relevance
“…3,25,26 One study has suggested that antioxidant defense mechanism deteriorates with age, and leaves the liver vulnerable to oxidative stress. 27 Our finding was consistent with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…3,25,26 One study has suggested that antioxidant defense mechanism deteriorates with age, and leaves the liver vulnerable to oxidative stress. 27 Our finding was consistent with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…Several patients had previously described risk factors for liver fibrosis progression such as obesity (27,28), use of cannabis (29), smoking(30), exposure to HBV (31) and excessive intake of alcohol (32). We found associations between advanced liver fibrosis and alcohol consumption, increased BMI and the presence of anti-HBc antibodies.…”
Section: Discussionsupporting
confidence: 52%
“…[2][3][4][5][6][7][8] Other parameters have been recently unearthed or remain controversial, such as steatosis, overweight, diabetes, and tobacco use. [9][10][11][12] Nevertheless, progression of fibrosis may occur in the absence of any identified profibrogenic factor, therefore warranting further research in that field.…”
mentioning
confidence: 99%